2003
DOI: 10.1093/jnci/djg075
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Pigmentation, Sun Exposure, and Risk of Cutaneous Malignant Melanoma in Women

Abstract: Our results confirm previous findings that hair color, number of nevi on the legs, and history of sunburn are risk factors for melanoma and suggest that use of a solarium is also associated with melanoma risk. Adolescence and early adulthood appear to be among the most sensitive age periods for the effects of sunburn and solarium use on melanoma risk. However, it may be too early to see the full effect of adult exposures in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
264
8
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(292 citation statements)
references
References 30 publications
12
264
8
8
Order By: Relevance
“…Kraemer et al, reported carcinoma of the tip of the tongue upto 6 % of cases while Goyal et al reported in 2 out of the 10 cases reported [12,13]. Incidence of internal malignancies like intracranial, bone marrow, stomach, testis, lungs and pancreas upto 10-20 fold higher than the normal population are reported [17,19]. Initially the skin shows slight diffuse erythema which is associated with scaling and small areas of hyperpigmentation resembling freckles seen as early as 1-2 year old, later skin atrophies with mottled pigmentation and telangiectasias mimicking chronic radio-dermatitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kraemer et al, reported carcinoma of the tip of the tongue upto 6 % of cases while Goyal et al reported in 2 out of the 10 cases reported [12,13]. Incidence of internal malignancies like intracranial, bone marrow, stomach, testis, lungs and pancreas upto 10-20 fold higher than the normal population are reported [17,19]. Initially the skin shows slight diffuse erythema which is associated with scaling and small areas of hyperpigmentation resembling freckles seen as early as 1-2 year old, later skin atrophies with mottled pigmentation and telangiectasias mimicking chronic radio-dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Malignancies appear in adolescence proving fatal in the third decade [8,9]. Cutaneous cancers i.e., BCC and SCC are the commonest cancers universally, occurs in old age while in teenage XP patients [19,20]. BCC is currently the most common cutaneous cancer in humans [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7,18 The lack of association between BMI or weight and melanoma risk in our pooled analyses is consistent with the findings of 5 5,10,12,15,16 of 8 other case-control studies, [5][6][7]10,12,13,15,16 and 7 17-23 of 8 cohort studies. [17][18][19][20][21][22][23][24] To our knowledge there are no previous studies that have examined the association between weight gain and risk of melanoma among women. Our pooled analyses excluded men because the original study aims of the analysis focused on sex steroid-related factors in women.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Interpretation of the results has been hampered by differences in methodology and inconsistent approaches to defining overweight and obesity. Moreover, only a few studies have examined associations according to histologic subtype 14,15,25 or menopausal status, 7,8 which may be important given the possible link between reproductive and hormonal factors and risk of melanoma in women.…”
mentioning
confidence: 99%